Validation and Reliability Analysis of the Spinal Deformity Study Group Classification for L5-S1 Lumbar Spondylolisthesis. Issue 21 (November 2015) - Bao, Hongda; Yan, Peng; Zhu, Weiguo; Bao, Mike; Li, Yang; Zhang, Zhen; Qiu, Yong; Zhu, Feng
Abstract : Study Design: An intra- and interobserver reliability study. Objective: To assess the intra- and interobserver reliability of the Spinal Deformity Study Group (SDSG) system for classifying adolescent and adult L5-S1 spondylolisthesis. Summary of Background Data: Reliability of the SDSG classification has only been previously validated in adolescent patients as performed by the SDSG study group investigators. Methods: A total of 80 patients with L5-S1 spondylolisthesis were included in this study. Only dysplastic and isthmic spondylolisthesis were included in this study. Long-cassette standing lateral radiographs of the spine and pelvis were obtained. All 80 cases were classified according to the SDSG classification by four observers. After a 2-week interval, the same classification was independently repeated by each observer with the cases in a different randomly assigned order. The Fleiss' κ coefficient was calculated to test the intra- and interobserver reliabilities of the SDSG classification. Results: The present study included all six types of SDSG classification. Overall intra- and interobserver agreements were 86.6% (κ: 0.830) and 73.3% (κ: 0.648), respectively. The intra- and interobserver agreements and repeatability associated with slip grade were 89.7% (κ: 0.824) and 87.7% (κ: 0.721), respectively. Regarding sacropelvic and spinal balance, intra- and interobserver agreements and repeatability were 83.7% (κ: 0.735) and 77.5% (κ: 0.602) for low-grade slips, and 90.75% (κ: 0.883) and 90.4% (κ: 0.851) for high-grade slips, respectively. Conclusion: Substantial intra- and interobserver reliability was found for the SDSG classification in L5-S1 lumbar spondylolisthesis. SDSG classification system is a simple and clear classification scheme incorporating spinopelvic parameters, which provides significant clinical utility. Level of Evidence: 3